2017
DOI: 10.1016/j.jplph.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Post-anthesis nitrate uptake is critical to yield and grain protein content in Sorghum bicolor

Abstract: Crops only use 50% of applied nitrogen (N) fertilizer creating N losses and pollution. Plants need to efficiently uptake and utilize N to meet growing global food demands. Here we investigate how the supply and timing of nitrate affects N status and yield in Sorghum bicolor (sorghum). Sorghum was grown in pots with either 10 mM (High) or 1 mM (Low) nitrate supply. Shortly before anthesis the nitrate supply was either maintained, increased 10-fold or eliminated. Leaf sheaths of sorghum grown with High nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Finally, it is also possible that grain N loading in Brachypodium Bd21-3 is mainly based on post-anthesis N uptake, rather than on N remobilization. A similar case has been reported for instance in sorghum 75,76 and in stay-green maize genotypes 77 . In the case of Brachypodium, the relative importance of post-anthesis NO 3 − uptake could be related to the non-domesticated nature of the species.…”
Section: Resultssupporting
confidence: 84%
“…Finally, it is also possible that grain N loading in Brachypodium Bd21-3 is mainly based on post-anthesis N uptake, rather than on N remobilization. A similar case has been reported for instance in sorghum 75,76 and in stay-green maize genotypes 77 . In the case of Brachypodium, the relative importance of post-anthesis NO 3 − uptake could be related to the non-domesticated nature of the species.…”
Section: Resultssupporting
confidence: 84%
“…This indicates that root N uptake efficiency may be a stable trait of wheat cultivars, being less affected by N availability. Possibly, N related gene expression, transport and metabolic pathways might have varied among cultivars (Worland et al, 2017;Sestili et al, 2018), resulting in increased root N uptake efficiency in modern cultivars. Reduced RLD but increased root N uptake efficiency during several decades of selection for yield was also reported by Aziz et al (2017) in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…This partitioning of N within sorghum plant parts has been documented to follow the same trend with low-and high-input treatments, as well as under rain-fed or irrigated conditions (McHenry, 2016). Contrary to these results, it has been reported that leaf sheaths and leaf blades are the predominant N sink in sorghum, and high levels of N application (10 mM KNO 3 ) given at 55 days after sowing resulted in a fourfold higher nitrate concentration in leaf sheaths compared to the control (Worland et al, 2017). Moreover, under N-deficient conditions, the demand for N from the leaves becomes proportionally greater than that from the stem (van Oosterom et al, 2010a).…”
Section: Nitrogen Partitioning and Stay-green Trait In Sorghummentioning
confidence: 89%